AN INVESTIGATION INTO LEXICAL CONTENTS IN ENGLISH STANDARDIZED TESTS - Dinh Thi Mai Anh, Tran Ba Tien* (Tạp chí Khoa học)
This paper aims to critically analyze lexical contents in national English standardized tests in an EFL context. Using the Compleat Lexical Tutor corpus tool, the lexical profiles of these exams are meticulously examined, revealing the distribution of word types, tokens, and word families across various frequency bands. The findings show that the lexical demands in the standardized tests are inconsistent across the examined years, with a predominant emphasis on high-frequency words and recognition-based knowledge. The study concludes by offering recommendations to improve the test design, advocating for a more balanced approach that better reflects the complexities of vocabulary knowledge.